An effective, low-cost method for achieving and maintaining hypoxia during cell culture studies. (October 2015) - Bakmiwewa, Supun M.; Heng, Benjamin; Guillemin, Gilles J.; Ball, Helen J.; Hunt, Nicholas H.
Here we report a simple new method for exposing cells to normoxic and hypoxic conditions using vacuum bags, normally employed for food storage, to establish and maintain low oxygen levels in vitro. Vacuum bags were gassed with a mixture containing specified levels of oxygen, then sealed, creating a hypoxic microenvironment for cells cultured in flasks placed therein. Oxygen levels in the gas mixture and culture medium in flasks inside the sealed bags equilibrated after two hours of incubation. The vacuum bags maintained low oxygen levels (either <2% or 5%) in medium for at least 4 days. Human fetal astrocytes grew normally in flasks for at least 4 days in a 5% oxygen/ 5% CO2 / 90% nitrogen atmosphere, but viability decreased at <2% oxygen. Vacuum bags can accommodate varying oxygen levels that would otherwise require systems with separate chambers or modules, but are less useful when repeated experimental manipulations of individual cultures are required.